Effect of solarization on nutrient availability, enzyme activity and growth of pomegranate (Punica granatum) air-layered on various potting mixtures - Maity, Ashis; Sharma, Jyotsana; Jadhav, V T; Babu, K Dhinesh; Chandra, Ram (The Indian Journal of Agricultural Sciences, 2012)
Pomegranate air layers are generally raised on potting mixture consisting of soil, sand and FYM/vermicompost in the nursery. Increasing concern over the impact of chemical fertilizers and pesticides on the environment for raising disease- free vigorous planting materials necessitate the exploitation of renewable solar energy for disinfecting growth medium and at the same time its enrichment with respect to plant nutrients. Solarization of components in the potting mixture (soil: sand: farmyard manure, 1:1:1, soil: sand: vermicompost, 1:1:1 and soil: sand, 1:1) and their use in various combinations [soil (nonsolarized, NS):sand (nonsolarized, NS):FYM (nonsolarized, NS); soil (solarized, S):sand (solarized, S):FYM (solarized, S); soil (S):sand (S):FYM (NS); soil (NS):sand (NS):vermicompost (NS); soil (S):sand (S):vermicompost (S); soil (S):sand (S):vermicompost (NS); soil (NS):sand (NS); soil (S):sand (S)] was evaluated for production of vigorous air- layer planting materials of pomegranate. Mixing of farmyard manure to solarized soil-sand media significantly increased available nutrient status (particularly P and K), alkaline and acid phosphatase activity and plant growth and vigour as indicated by chlorophyll content (SPAD value), photosynthetic and transpiration rate. Weed population also got reduced significantly. On the contrary, mixing of vermicompost to solarized soil-sand media did not result in any positive impact on plant growth over non-solarized and solarized soil-sand-vermicompost mixtures. With only soil-sand as potting media, non-solarized media recorded higher plant growth, nutrient availability (P and K) and enzyme activity (alkaline phosphatase and acid phosphatase) over solarized one but reduction in dehydrogenase activity and weed population were noted upon solarization of the said medium.